Banquet Service Quality in Enhancing Hotel Customer Satisfaction - Tien-Tsai Pan; Jiye Margate (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: This study aims to examine the influence of banquet service quality on customer satisfaction at Hotel Ratu Mayang Garden Pekanbaru by analyzing service responsiveness, professionalism, facility readiness, and event coordination in supporting customer satisfaction and hotel service competitiveness within the hospitality industry. Methodology: This study employed a quantitative associative causal research design using survey methods and structured questionnaires with Likert scales. Data were collected from 81 banquet customers selected through proportional sampling techniques. Research instruments included validity and reliability testing using Product Moment correlation and Cronbach’s Alpha. Data analysis used descriptive statistics, simple linear regression, and t-test analysis. Main Findings: The findings revealed that banquet service quality significantly influenced customer satisfaction at Hotel Ratu Mayang Garden Pekanbaru. Employee professionalism, responsiveness, reliability, and facility readiness were perceived positively by respondents and contributed to higher satisfaction levels. Regression analysis showed a significant positive relationship between banquet service quality and customer satisfaction, indicating that improved banquet services enhance customer trust, loyalty, and hotel competitiveness. Novelty/Originality of this study: This study specifically focuses on banquet services as strategic hospitality operations influencing customer satisfaction, unlike previous studies emphasizing general hotel services. The study integrates banquet operational dimensions including responsiveness, professionalism, event coordination, and facility readiness within customer satisfaction analysis, thereby contributing new perspectives to hospitality service quality and banquet management literature.